Survey of the species of ornamental fish available in pet trade markets in Basrah province - Qasim, Audai (Iraqi Journal of Aquaculture, 2024)
This study represents the first attempt to evaluate exotic ornamental fish species in Shops specializing in ornamental fish. This study was carried out in the province of Basrah between 2023 and 2024. The visits were made to Shops specializing in ornamental fish spread throughout Basrah province. The species present were documented and classified based on their respective families. The study recorded 46 species of ornamental fish belonging to 20 families, including five marine species, exotic fish and no local species. However, the study recognized certain species that are hazardous to the environment if infiltrated, and the study did not record species that threatened humans during the study period. However, there is a need to improve the monitoring and management of dangerous species, as some of them are among the most popular aquarium fish traded worldwide. In addition to the plans and efforts made by the government through the management of its institutions. Researchers and hobbyists should be involved, along with state institutions, because of the importance of their role in the successful monitoring and management of fish introductions. If new fish species need to be imported in the future, a risk assessment should be adopted to assist in making recommendations to guide management decisions. Exotic fish often cause harm to fish stocks, environmental damage, and sometimes a threat to humans. Therefore, the ornamental fish trade must impose trade restrictions and legislation to regulate this trade. To reduce the negative effects resulting from the entrance of non-native species.